Unpacking the Dynamics of Curvature and Torsion Using JavaScript - Dhakal, Bed Prasad (Educational Journal, 2026)
Understanding the curvature and torsion is a fundamental concept in differential geometry, which is often a struggle for students due to its only symbolic computation. This Phenomenography study explores how interactive digital tools, specifically JavaScript-based interactive simulations, enhance students understanding on the dynamics of curvature and torsion. TPACK framework and connectivism   is used as theoretical framework in this study to answer the research question” How do students understand the dynamics of curvature and torsion using JavaScript based mathematical simulation”. The finding of this study is based on thirteen master’s students at Tribhuvan University, Nepal during 2024 academic year. This study finds that the interactive tools like JavaScript significantly improve students’ conceptual clarity on the dynamics of curvature and torsion, integrating concept definition with concept image: "curvature is bending along straight line, torsion is distortion along the plane”.